Kinetic measurements to investigate the oxygen-sensing properties of plant cysteine oxidases - Dirr, A; Gunawardana, DM; Flashman, E (Springer Nature, 2023)
Enzymatic O2 sensors transduce the availability of O2 within the cell into a physiological, typically adaptive response. One such O2-sensing enzymatic family is the N-terminal cysteine dioxygenases in plants (plant cysteine oxidases [PCOs]). In vitro kinetic studies have determined the O2-sensing capacity of PCOs. Here we describe the rationale and experimental protocol for an assay with which the O2 sensitivity of Arabidopsis thaliana PCOs (AtPCOs) can be measured. We explain each step from the recombinant protein synthesis of AtPCOs to the steady-state kinetic assays of AtPCOs for primary substrate and O2 from which kinetic parameters can be derived. The same techniques can be applied to other N-terminal cysteine thiol dioxygenases, e.g. 2-aminoethanethiol dioxygenase (ADO), and similar principles can be applied to determine kinetic characteristics of other oxygenase enzymes towards O2.